Development of biological control strategies for collar rot and early leaf spot for organic cultivation of groundnut - PARDEEP KUMAR, DATA RAM, SHRI KISHAN BAIRWA* and (Indian Phytopathology, 2016)
To develop a suitable disease management package in groundnut using biocontrol agents and botanicals, a field trial was conducted during 2011 to 2014 at Hanumangarh district of Rajasthan. The treatment module consisting of seed treatment with Trichoderma viride at 10g kg-1 seed plus furrow application of FYM (250 kg ha-1) enriched with 4.0 kg T. viride (at time of sowing) followed by two foliar applications of neem seed kernel extract (5 per cent) at 45 and 60 days after sowing gave maximum reduction (76.45%) and least incidence (6.42%) of collar rot disease with highest pod yield (2310 kg ha-1) as well as maximum net profit. This module also showed significant (P=0.05) reduction of early leaf spot disease (60.54%) over control. Integration of bioagents and fungicides also proved effective for disease management in groundnut crop. The module comprising of seed treatment with T. viride at 10g kg-1 seed plus furrow application of FYM (250 kg ha-1) enriched with 4.0 kg T. viride (at time of sowing) and foliar spray of hexaconazole (0.1 per cent) at 45 and 60 days after sowing was observed to be the most effective treatment to manage early leaf spot disease of the crop.